A nanocomposite powder coating and its preparation method and application

Through the production method of nano composite powder coating, the problem of low -temperature anti -high temperature and insufficient stretch strength in existing technologies have been solved, and efficient metal surface protection has been achieved. performance.

CN116254031BActive Publication Date: 2025-01-24CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310469602.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-01-24
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the friction wear and corrosion resistance of the coating, especially low high temperature resistance, and insufficient tensile strength and firmness of the coating.

Method used

Using the production method of nanocomposite powder coating, polymer powder particles, additives and inorganic nano-micron particles are extruded and crushed through injection molding to form microsphere powder particles with uniform composition, and are formed through electrostatic spraying and thermal melting treatment. Nanocomposite powder coating.

Benefits of technology

It achieves the high temperature resistance, friction and wear resistance and corrosion resistance of the coating, improves the glass transition temperature and heat resistance of the coating, and at the same time enhances the tensile strength and solidity of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116254031B_ABST
    Figure CN116254031B_ABST
Patent Text Reader

Abstract

The present invention provides a nano-composite powder coating and a preparation method and application thereof, wherein the preparation method comprises crushing, stirring and mixing 60-90 parts by weight of polymer powder particles, 5-15 parts by weight of auxiliary agents and 20-40 parts by weight of inorganic nano-micro particles to form a particle mixture; injection molding, extruding and crushing the particle mixture to form microsphere powder particles with uniform components; using an electrostatic spraying method to form a microsphere particle accumulation covering layer on a metal surface with the microsphere powder particles; performing a heat melting treatment on the microsphere particle accumulation covering layer formed on the metal surface to obtain the nano-composite powder coating. The nano-composite powder coating provided by the present invention is used as a metal surface protective layer, which can protect the metal surface and produce high temperature resistance, friction and wear resistance and corrosion resistance effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano composite powder coating and a preparation method and application thereof, belonging to the technical field of chemical coatings. Background Art

[0002] Powder spraying is an important technology for surface decoration, protection, stealth or invisibility. Electrostatic powder spraying is an important spraying technology for metal surfaces. Powder materials are formed into charged particles through ultra-high pressure instantaneous ionization air flow and sprayed on the metal surface. After heat treatment, the surface melts and the leveling coating is tightly bonded to form a high-temperature resistant, flat and wear-resistant coating, which produces high-temperature resistance, friction and wear resistance, corrosion resistance and high-efficiency protection effects on the metal surface.

[0003] The existing technology mainly focuses on improving the friction and wear resistance and corrosion resistance of the coating. Therefore, high molecular plastics with good fluidity and low friction coefficient, such as polyethylene and polypropylene coatings, are selected to achieve practical spraying effects. However, the high temperature resistance of the coating is low, and the tensile strength of the coating is reduced by adding high temperature resistant inorganic phases (Shi Guojun, Yuan Yue, Li Cui, Shen Jianyi. Study on the wear and heat resistance of glass microsphere reinforced ultra-high molecular weight polyethylene [J]. Journal of Tribology, 2015, 35(06): 714-723.).

[0004] The injection molding process is to melt the thermoplastic resin material or resin composite material at a certain melting temperature, and then extrude the material under a certain pressure to form a sample with uniform texture. The heating, melting and cold extraction process of injection molding can make the polymer material reach the best performance state. By crushing after injection molding, the various properties of the material can be maintained, and the bonding force between the various phases of the composite material can be enhanced.

[0005] The existing technology uses ultrafine powders of polymers and their inorganic mixtures to improve the surface spraying effect. For example, active metal powder is mixed into ultrafine polymer powder to regulate the mutual permeability between metal powder atoms and metal surface atoms to improve the coating adhesion and consolidation effect. However, the coating thickness is low, the leveling property is poor, and the firmness and strength are not high enough.

[0006] Therefore, providing a new type of nano-composite powder coating and its preparation method and application has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0007] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide a method for preparing a nano-composite powder coating.

[0008] Another object of the present invention is to provide a nano-composite powder coating, which is prepared by the above-mentioned method for preparing the nano-composite powder coating.

[0009] Another object of the present invention is to provide the use of the above-mentioned nanocomposite powder coating as a metal surface protective layer.

[0010] In order to achieve the above objectives, on the one hand, the present invention provides a method for preparing a nano-composite powder coating, wherein the method for preparing the nano-composite powder coating comprises:

[0011] Step 1: 60-90 parts by weight of polymer powder particles, 5-15 parts by weight of additives and 20-40 parts by weight of inorganic nano-micro particles are crushed, stirred and mixed to form a particle mixture;

[0012] Step 2: injecting and extruding the particle mixture (the extrusion process makes the particles tightly bonded) and crushing to form microsphere powder particles with uniform components;

[0013] Step 3: using an electrostatic spraying method to make the microsphere powder particles form a microsphere particle accumulation covering layer on the metal surface;

[0014] Step 4: performing a heat-melting treatment on the microsphere particle accumulation covering layer formed on the metal surface to obtain the nano-composite powder coating.

[0015] As a specific embodiment of the above-mentioned production method of the present invention, the polymer powder particles are ultrafine plastic polymer particles, and the ultrafine plastic polymer particles include one polymer particle with an apparent particle size of 20-75 μm or a mixed particle of at least two different polymer particles.

[0016] As a specific embodiment of the above-mentioned preparation method of the present invention, the polymer powder particles include one or a combination of 30-75 μm polyamide particles, 20-50 μm polyolefin particles and 30-75 μm maleic anhydride particles.

[0017] As a specific embodiment of the above-mentioned production method of the present invention, the polymer powder particles include 10-50 parts by weight of polyamide particles with a size of 30-75 μm, 10-50 parts by weight of polyolefin particles with a size of 20-50 μm and 10-50 parts by weight of maleic anhydride particles with a size of 30-75 μm.

[0018] As a specific embodiment of the above-mentioned preparation method of the present invention, the polyamide particles include nylon powder particles, preferably one of nylon 6 particles, nylon 66 particles, nylon 11 particles, and nylon 4 particles, or a mixture of two of the particles. The use of polyamide particles can improve the glass transition temperature and heat resistance of the nanocomposite powder coating.

[0019] As a specific embodiment of the above-mentioned production method of the present invention, the polyolefin particles include polyethylene particles and / or polypropylene particles.

[0020] As a specific embodiment of the above-mentioned production method of the present invention, the polymer powder particles include 20-40 parts by weight of nylon 6 particles (also referred to as nylon 6 resin particles) and / or nylon 66 particles (also referred to as nylon 66 resin particles), 20-40 parts by weight of maleic anhydride particles, and 20-40 parts by weight of polyethylene resin particles (i.e., polyethylene particles), and the total amount of these particles needs to be 60-90 parts by weight.

[0021] The polymer powder particles used in the present invention are all conventional materials and can be obtained commercially. For example, the nylon 6 particles, nylon 66 particles and polyethylene resin particles can all be purchased from Dongguan Huachuang Plastic Chemical Co., Ltd., and the maleic anhydride particles can be purchased from Yuyao Bangchao Plastic Chemical Co., Ltd.

[0022] As a specific embodiment of the above-mentioned production method of the present invention, the inorganic nano-micron particles include oxide powder particles and / or layered structure powder particles with a size of 10 nm-60 μm.

[0023] As a specific embodiment of the above-mentioned manufacturing method of the present invention, the oxide powder particles include oxide powder particles with a size of 20 nm-20 μm.

[0024] As a specific embodiment of the above-mentioned production method of the present invention, the oxide powder particles include SiO2 powder particles and / or Al2O3 powder particles.

[0025] As a specific embodiment of the above-mentioned production method of the present invention, the layered structure powder particles include layered structure powder particles of 50nm-40μm.

[0026] As a specific embodiment of the above-mentioned production method of the present invention, the layered structure powder particles include one or a combination of mica powder particles, montmorillonite particles, kaolin particles, and graphite powder particles.

[0027] As a specific embodiment of the above-mentioned production method of the present invention, the inorganic nano-micron particles include any one of 50nm-20μm Al2O3 particles, 10nm-60nm SiO2 particles, 50nm-40μm mica powder particles, and 5μm-60μm graphite powder particles, or a mixture of at least two of them.

[0028] As a specific embodiment of the above-mentioned production method of the present invention, the inorganic nano-micron particles include 5-10 parts by weight (preferably 5 parts by weight) of Al2O3 particles of 50nm-20μm, 5-10 parts by weight (preferably 5 parts by weight) of SiO2 particles of 10nm-60nm, 0-30 parts by weight of mica powder particles of 50nm-40μm, and 0-30 parts by weight of graphite powder particles of 5μm-60μm, and the total amount of these particles needs to be ensured to be 20-40 parts by weight.

[0029] The inorganic nano-micron particles used in the present invention are also conventional materials and can be obtained commercially. For example, in some embodiments of the present invention, the Al2O3 particles are industrial grade first-class products, the SiO2 particles are industrial grade products, the mica powder particles are sericite powder, and the graphite powder particles are industrial grade products.

[0030] As a specific embodiment of the above-mentioned production method of the present invention, the auxiliary agent includes 1-5 parts by weight of a leveling agent, 1-5 parts by weight of a silane coupling agent and / or a titanate coupling agent, and 1-5 parts by weight of an antioxidant.

[0031] As a specific implementation of the above-mentioned preparation method of the present invention, the amount of the silane coupling agent used is 0-3 parts by weight.

[0032] As a specific embodiment of the above-mentioned manufacturing method of the present invention, the leveling agent includes a polyacrylic acid or polyacrylate leveling agent.

[0033] As a specific implementation of the above-mentioned preparation method of the present invention, wherein the silane coupling agent includes KH550 type or KH570 type silane coupling agent.

[0034] As a specific embodiment of the above-mentioned preparation method of the present invention, the antioxidant includes a phosphite antioxidant. In some embodiments of the present invention, the phosphite antioxidant can be, for example, the antioxidant AT-626 produced by Shandong Yousuo Chemical Technology Co., Ltd.

[0035] The leveling agent, silane coupling agent, titanate coupling agent and antioxidant used in the present invention are also conventional substances and can be obtained commercially.

[0036] As a specific embodiment of the above-mentioned preparation method of the present invention, the polymer powder particles are mixed particles of 30 parts by weight of nylon 6 resin particles, 30 parts by weight of maleic anhydride particles, 30 parts by weight of polyethylene resin particles and 30 parts by weight of nylon 66 resin particles;

[0037] The inorganic nano-micron particles are mixed particles of 5 parts by weight of Al2O3 particles with a size of 50nm-20μm, 5 parts by weight of SiO2 particles with a size of 10nm-60nm and 20 parts by weight of graphite powder particles with a size of 5μm-60μm;

[0038] The auxiliary agent comprises 5 parts by weight of a polyacrylic acid leveling agent or a polyacrylate leveling agent, 5 parts by weight of a KH550 or KH570 silane coupling agent and 5 parts by weight of a phosphite antioxidant.

[0039] As a specific embodiment of the above-mentioned preparation method of the present invention, in step 1, 60-90 parts by weight of polymer powder particles, 5-15 parts by weight of additives and 20-40 parts by weight of inorganic nano-micro particles are crushed, stirred and mixed in an industrial mechanical mixer to form a particle mixture. The industrial mechanical mixer used in the present invention is an existing conventional equipment and can be obtained by commercial purchase.

[0040] As a specific embodiment of the above-mentioned production method of the present invention, step one also includes: drying the polymer powder particles for a certain period of time to keep the particles dry, and then crushing, stirring and mixing 60-90 parts by weight of the dried polymer powder particles, 5-15 parts by weight of the auxiliary agent and 20-40 parts by weight of the inorganic nano-micron particles to form a particle mixture.

[0041] As a specific embodiment of the above-mentioned production method of the present invention, in step 2, the particle mixture is injection-molded, extruded and crushed by an injection molding machine to form microsphere powder particles with uniform components. The injection molding machine is an existing conventional equipment and can be obtained by commercial purchase.

[0042] As a specific embodiment of the above-mentioned production method of the present invention, in step 1, the particle mixture is nano-composite powder particles, and the size range of the particles is 20nm-75μm.

[0043] As a specific embodiment of the above-mentioned production method of the present invention, in step 2, after the pulverization, the pulverized product is further classified and screened to obtain microsphere powder particles with a size not greater than 50 μm.

[0044] As a specific embodiment of the above-mentioned production method of the present invention, step three specifically includes: the microsphere powder particles are subjected to the ultra-high voltage of the electrostatic spray gun to instantly form charged microsphere particles, and then the charged microsphere particles are sprayed onto the metal surface through the spray gun nozzle of the electrostatic spray gun, and the charged microsphere particles generate electrostatic adsorption on the metal surface to form a microsphere particle accumulation covering layer.

[0045] As a specific embodiment of the above-mentioned production method of the present invention, in step three, the thickness of the microsphere particle accumulation covering layer obtained after one electrostatic spraying is not less than 300 μm.

[0046] As a specific implementation of the above-mentioned production method of the present invention, in step 4, the temperature of the hot melting treatment is 180-230°C.

[0047] As a specific implementation of the above-mentioned production method of the present invention, in step 4, the heat melting treatment is carried out in an oven.

[0048] On the other hand, the present invention further provides a nano-composite powder coating, wherein the nano-composite powder coating is prepared by the above-mentioned method for preparing the nano-composite powder coating.

[0049] As a specific embodiment of the nano-composite powder coating of the present invention, the nano-composite powder coating is a high temperature resistant and wear resistant coating, the high temperature resistance of which reaches 150° C. and the friction coefficient is lower than 0.4.

[0050] As a specific embodiment of the nano-composite powder coating of the present invention, the thickness of the nano-composite powder coating is not less than 300 μm.

[0051] In yet another aspect, the present invention also provides the use of the above-mentioned nanocomposite powder coating as a metal surface protective layer.

[0052] As a specific implementation of the above application of the present invention, the nanocomposite powder coating is used as a surface protection layer of a metal pipe rod. In some embodiments of the present invention, the metal pipe rod is a metal pipe rod used in the field of petroleum and petrochemicals.

[0053] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0054] In the second step of making the nano-composite powder coating of the present invention, the particle mixture is injection-molded, extruded and crushed to form microsphere powder particles with uniform components. The voids of the microsphere powder particles obtained in this way are reduced, thereby producing barrier properties; in addition, the microsphere powder particles can be more evenly coated on the metal surface, producing a protective effect of high temperature resistance, friction resistance, wear resistance and corrosion resistance on the metal surface.

[0055] The nano composite powder coating provided by the present invention is used as a metal surface protective layer, which can protect the metal surface and produce high temperature resistance, friction and wear resistance and corrosion resistance effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0057] Figure 1a-1f This is a graph of the friction coefficient of the nanocomposite powder coating provided by Examples 1 to 5 and Comparative Example 1 obtained in Test Example 2 of the present invention.

[0058] Figure 2 This is a SEM image of the microsphere powder particles obtained in step 2 of Example 3 of the present invention. DETAILED DESCRIPTION

[0059] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units that are not explicitly listed or inherent to these processes, methods, products or devices.

[0060] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0061] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0062] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0063] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0064] In the present invention, if not specifically stated, the term "two" used in this specification means "at least two".

[0065] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0066] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0067] Example 1

[0068] This embodiment provides a nanocomposite powder coating, which is prepared by a preparation method comprising the following specific steps:

[0069] Step 1: 90 parts by weight of polymer powder particles, 11 parts by weight of additives and 40 parts by weight of inorganic nano-micro particles are crushed, stirred and mixed in an industrial mechanical mixer to form a particle mixture;

[0070] The polymer powder particles are composed of 30 parts by weight of nylon powder particles (nylon 6 particles, 70 μm), 30 parts by weight of maleic anhydride particles (70 μm) and 30 parts by weight of polyethylene particles (40 μm);

[0071] The auxiliary agent is composed of 5 parts by weight of a polyacrylate leveling agent, 3 parts by weight of a KH570 silane coupling agent and 3 parts by weight of an antioxidant AT-626;

[0072] The inorganic nano-micron particles are composed of 5 parts by weight of metal oxide Al2O3 particles with a size of 50nm-20μm, 5 parts by weight of non-metal oxide SiO2 particles with a size of 10nm-60nm, 15 parts by weight of graphite powder particles with a size of 5μm-60μm, and 15 parts by weight of mica powder particles with a size of 50nm-40μm;

[0073] Step 2: using an injection molding machine to perform injection molding and extrusion on the particle mixture (the extrusion process allows the particles to be tightly bonded) and crushing to form microsphere powder particles with uniform components;

[0074] Step 3: Classify and screen the microsphere powder particles, preferably nano-composite powder coating particle materials;

[0075] Step 4: Metal substrate treatment and surface electrostatic spraying

[0076] (1) Sand blasting:

[0077] White corundum with a particle size of 100-150 μm is sprayed on the surface of the metal substrate by compressed air to form a certain roughness on the surface of the metal substrate;

[0078] (2) Preheating:

[0079] The sandblasted metal substrate was placed in a hot oven preheated to 150°C for 1 min;

[0080] (3) Surface electrostatic spraying:

[0081] After the temperature of the metal substrate is constant, the substrate is taken out and immediately subjected to surface electrostatic spraying, including: the nanocomposite powder coating particle material is subjected to the ultra-high voltage of the electrostatic spray gun to instantly form charged microsphere particles, and then the charged microsphere particles are sprayed onto the metal surface through the spray gun nozzle of the electrostatic spray gun, and the charged microsphere particles are electrostatically adsorbed on the metal surface to form a microsphere particle accumulation covering layer;

[0082] Step 5: Carefully transfer the metal substrate with the microsphere particle accumulation covering layer formed on the surface to a preheated oven and perform melt curing and crosslinking at a temperature of 230° C. for 20 minutes to obtain the nanocomposite powder coating.

[0083] Example 2

[0084] This embodiment provides a nanocomposite powder coating, which differs from Embodiment 1 only in that:

[0085] The inorganic nano-micron particles are composed of 5 parts by weight of metal oxide Al2O3 particles with a size of 50nm-20μm, 5 parts by weight of non-metal oxide SiO2 particles with a size of 10nm-60nm and 15 parts by weight of mica powder particles with a size of 50nm-40μm, that is, the inorganic nano-micron particles are 25 parts by weight.

[0086] Example 3

[0087] This embodiment provides a nanocomposite powder coating, which differs from Embodiment 1 only in that:

[0088] The inorganic nano-micron particles are composed of 5 parts by weight of metal oxide Al2O3 particles with a size of 50nm-20μm, 5 parts by weight of non-metal oxide SiO2 particles with a size of 10nm-60nm, and 15 parts by weight of graphite powder particles with a size of 5μm-60μm, that is, the inorganic nano-micron particles are 25 parts by weight.

[0089] Example 4

[0090] This embodiment provides a nanocomposite powder coating, which differs from Embodiment 1 only in that:

[0091] The inorganic nano-micron particles are composed of 5 parts by weight of metal oxide Al2O3 particles with a size of 50nm-20μm, 5 parts by weight of non-metal oxide SiO2 particles with a size of 10nm-60nm, and 20 parts by weight of graphite powder particles with a size of 5μm-60μm, that is, the inorganic nano-micron particles are 30 parts by weight.

[0092] Example 5

[0093] This embodiment provides a nanocomposite powder coating, which differs from Embodiment 1 only in that:

[0094] The polymer powder particles consist of 15 parts by weight of nylon 6 particles (70 μm), 15 parts by weight of nylon 66 particles (70 μm), 30 parts by weight of maleic anhydride particles (70 μm) and 30 parts by weight of polyethylene particles (70 μm).

[0095] Comparative Example 1

[0096] This comparative example provides a nanocomposite powder coating, which differs from Example 1 only in that:

[0097] The injection molding, extrusion and pulverization operations are not performed, but the particle mixture is directly graded and screened, and the surface is electrostatically sprayed using the preferred nano-composite powder coating particle material as the raw material.

[0098] Test Example 1

[0099] This test example observed the appearance of the nanocomposite powder coatings provided in Examples 1 to 5 and Comparative Example 1, and measured or tested their thickness, pencil hardness, adhesion, impact strength, resistance to 1 mol / L sulfuric acid, resistance to 1 mol / L NaOH, resistance to moisture and heat, and pencil hardness, adhesion and impact strength of the nanocomposite powder coating after treatment at 150°C by conventional methods such as those specified in GB / T1764-79, GB / T9286-98, GB / T6739-2006 and GB / T1732-1993. The test results are shown in Table 1 below.

[0100] Table 1

[0101]

[0102] It can be seen from Table 1 above that the surface of the nanocomposite powder coatings provided by Examples 1 to 5 of the present invention is smooth, uniform in color, and free of bubbles, cracks, and shrinkage cavities; the thickness thereof is all above 300 μm, the pencil hardness thereof can reach 5H, and the adhesion thereof is all level 0; the coating is intact under the impact condition of 40 kg*cm, indicating that the coating has excellent impact strength; the nanocomposite powder coating has excellent acid and alkali resistance, indicating that the coating has excellent corrosion resistance; in addition, the nanocomposite powder coating also has excellent moisture and heat resistance, and the temperature resistance thereof can reach 150°C;

[0103] As can be seen from Table 1 above, compared with the nanocomposite powder coatings provided in Examples 1 to 5 of the present invention, the thickness of the nanocomposite powder coating provided in Comparative Example 1 is less than 300 μm, the pencil hardness is only 4H, and the coating is intact under an impact condition of 30 kg*cm, indicating that its impact strength is poor, and under the same acidic or alkaline conditions, its acid and alkali resistance are also poor, which shows that when the nanocomposite powder coating is prepared in the present invention, an injection molding machine is used to injection-mold and extrude the particle mixture, which can enhance the compatibility between the powder coating particles and make the coating attached to the surface of the substrate more uniform, thereby improving the impact strength, corrosion resistance and moisture and heat resistance of the obtained nanocomposite powder coating.

[0104] Test Example 2

[0105] In this test example, friction tests were performed on the nano-composite powder coatings provided in Examples 1 to 5 and Comparative Example 1, respectively. The friction test was a UMT reciprocating test. During the test, a low-carbon steel ball with a diameter of 10 mm was selected as the upper sample, and the lower sample was the nano-composite powder coating described above. The test conditions were: load 5N, frequency 2Hz, reciprocating friction distance 6mm and time 20min.

[0106] The friction coefficient of the nanocomposite powder coating provided by Examples 1 to 5 and Comparative Example 1 obtained in this test example is shown in FIG. Figure 1a-1f As shown. Figure 1a-1f It can be seen that the friction coefficients of the nanocomposite powder coatings provided in Examples 1 to 5 of the present invention and Comparative Example 1 are all lower than 0.4, while the friction coefficient of the nanocomposite powder coating provided in Comparative Example 1 is lower in the early stage of the friction test, but then its friction coefficient is significantly improved and can reach about 0.5. This shows that when the nanocomposite powder coating is prepared by the present invention, an injection molding machine is used to injection-mold and extrude the particle mixture, so that the powder filler particles can be fully melted and the void ratio between the particles can be reduced, thereby making the roughness of the coating surface smaller and effectively reducing the friction coefficient.

[0107] Test Example 3

[0108] In this test example, the microsphere powder particles obtained in step 2 of Example 3 were subjected to SEM analysis. The obtained SEM image is as follows Figure 2 As shown. Figure 2 It can be seen that the powder particles are kneaded into spheres, indicating that the compatibility between the component particles is very good. At the same time, the combination into spheres helps the particles to be arranged more closely and enhances the surface properties of the coating.

[0109] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A method for preparing a nanocomposite powder coating, characterized in that: The method for preparing the nanocomposite powder coating comprises: Step 1: 60-90 parts by weight of polymer powder particles, 5-15 parts by weight of additives and 20-40 parts by weight of inorganic nano-micro particles are crushed, stirred and mixed to form a particle mixture; The polymer powder particles include one or a combination of 30-75 μm polyamide particles, 20-50 μm polyolefin particles and 30-75 μm maleic anhydride particles, and the polyamide particles include one or a mixture of nylon 6 particles, nylon 66 particles, nylon 11 particles and nylon 4 particles; The inorganic nano-micron particles include oxide powder particles of 10nm-60μm and layered structure powder particles, wherein the layered structure powder particles are layered structure powder particles of 50nm-40μm, including mica powder particles, montmorillonite particles, kaolin particles, graphite powder particles, or a combination of several thereof; The auxiliary agent includes 1-5 parts by weight of a leveling agent, 1-5 parts by weight of a silane coupling agent and / or a titanate coupling agent, and 1-5 parts by weight of an antioxidant, the leveling agent includes a polyacrylic acid or polyacrylate leveling agent, and the silane coupling agent includes a KH550 or KH570 silane coupling agent; Step 2: injecting and extruding the particle mixture and crushing it to form microsphere powder particles with uniform components; wherein the size of the microsphere powder particles is not greater than 50 μm; Step 3: using an electrostatic spraying method to make the microsphere powder particles form a microsphere particle accumulation covering layer on the metal surface, specifically comprising: the microsphere powder particles are subjected to the ultra-high voltage of the electrostatic spray gun to instantly form charged microsphere particles, and then the charged microsphere particles are sprayed onto the metal surface through the spray gun nozzle of the electrostatic spray gun, and the charged microsphere particles are electrostatically adsorbed on the metal surface to form a microsphere particle accumulation covering layer, and the thickness of the microsphere particle accumulation covering layer obtained after one electrostatic spraying is not less than 300 μm; Step 4: performing a heat-melting treatment on the microsphere particle accumulation covering layer formed on the metal surface to obtain the nano-composite powder coating; wherein the heat-melting treatment temperature is 180-230°C.

2. The method according to claim 1, characterized in that: The polyolefin particles include polyethylene particles and / or polypropylene particles.

3. The method according to claim 1, characterized in that: The oxide powder particles include oxide powder particles with a size of 20 nm-20 μm.

4. The method according to claim 3, characterized in that: The oxide powder particles include SiO2 powder particles and / or Al2O3 powder particles.

5. The method according to claim 1, characterized in that: The antioxidant includes a phosphite antioxidant.

6. A nanocomposite powder coating, characterized in that: The nanocomposite powder coating is prepared by the method for preparing the nanocomposite powder coating according to any one of claims 1 to 5.

7. The nanocomposite powder coating according to claim 6, characterized in that: The nano composite powder coating is a high temperature resistant and wear resistant coating, the high temperature resistance thereof reaches 150° C., and the friction coefficient is lower than 0.

4.

8. The nanocomposite powder coating according to claim 6 or 7, characterized in that: The thickness of the nanocomposite powder coating is not less than 300 μm.

9. Use of the nanocomposite powder coating according to any one of claims 6 to 8 as a metal surface protective layer.

Citation Information

Patent Citations

  • Polypropylene powder coating as well as preparation method and application thereof

    CN115895348A